Development of Health Education Media About Cultural Practices of The Palu Indigenous Culture Related to Breastfeeding for Postpartum Women Who Have Been Caring at Home - Jurana, Jurana; Masulili, Fitria (Poltekkes Kemenkes Palu, 2023)
The practice of providing appropriate breastfeeding for the first 6 months of life is the most important and cost-effective thing to reduce morbidity and mortality rate toward children. However, the obedience of exclusive breastfeeding in some of countries has not been satisfactory, so need the efforts to be done to increase its coverage. This study aims to develop and produces the health education media for cultural practices of the Palu indigenous culture related to breastfeeding for postpartum women who have been caring at home in Sigi Regency of Palu district in the form both of Kaili and Indonesian languages modules. This research is qualitative research with an ethnographic approach through two stages, namely: Phase I; Identification of cultural that influence the success of exclusive breastfeeding, Phase II; Development of health education media as a solution to the problem of an exclusive breastfeeding culture. The informants were taken by snowball method with a total seventeen of postpartum women, one informan key was from the community (Dukun), and one coordinator was the public health care nurse at the Biromaru Public Health Center. Data analysis in this ethnographic research is to find out the cultural themes, namely verbatim, keywords, and categories. The categories are the same and related to the sub-themes and the last step is to determine the theme itself. The research results is Phase I, Identifying both of myths and cultures that influence exclusive breastfeeding that still very well maintained, lack of womens' knowledge and womens' attitudes want to providing the exclusive breastfeeding. Phase II: development of health education media as a solution to the problem of exclusive reastfeeding culture based on the results of the phase I research. The conclusion is This study has developed a health education media related to the cultural practice of the Kaili tribe regarding exclusive breastfeeding to postpartum women who have been caring at home in Sigi Regency Palu district in the form both of Kaili and Indonesian language modules. In order to implement exclusive breastfeeding promotion media, by integrating it into the public health care program (Perkesmas), for maternal and child health programs and it need to involve community leaders by a cultural perspective.